Consensus Contouring Guidelines for Postoperative Stereotactic Body Radiation Therapy for Metastatic Solid Tumor Malignancies to the Spine - Redmond, Kristin J; Robertson, Scott; Lo, Simon S; Soltys, Scott G; Ryu, Samuel; McNutt, Todd; Chao, Samuel T; Yamada, Yoshiya; Ghia, Amol; Chang, Eric L; Sheehan, Jason; Sahgal, Arjun (International journal of radiation oncology, biology, physics, 2017)
To develop consensus contouring guidelines for postoperative stereotactic body radiation therapy (SBRT) for spinal metastases. Ten spine SBRT specialists representing 10 international centers independently contoured the clinical target volume (CTV), planning target volume (PTV), spinal cord, and spinal cord planning organ at risk volume (PRV) for 10 representative clinical scenarios in postoperative spine SBRT for metastatic solid tumor malignancies. Contours were imported into the Computational Environment for Radiotherapy Research. Agreement between physicians was calculated with an expectation minimization algorithm using simultaneous truth and performance level estimation with κ statistics. Target volume definition guidelines were established by finding optimized confidence level consensus contours using histogram agreement analyses. Nine expert radiation oncologists and 1 neurosurgeon completed contours for all 10 cases. The mean sensitivity and specificity were 0.79 (range, 0.71-0.89) and 0.94 (range, 0.90-0.99) for the CTV and 0.79 (range, 0.70-0.95) and 0.92 (range, 0.87-0.99) for the PTV), respectively. Mean κ agreement, which demonstrates the probability that contours agree by chance alone, was 0.58 (range, 0.43-0.70) for CTV and 0.58 (range, 0.37-0.76) for PTV (P<.001 for all cases). Optimized consensus contours were established for all patients with 80% confidence interval. Recommendations for CTV include treatment of the entire preoperative extent of bony and epidural disease, plus immediately adjacent bony anatomic compartments at risk of microscopic disease extension. In particular, a "donut-shaped" CTV was consistently applied in cases of preoperative circumferential epidural extension, regardless of extent of residual epidural extension. Otherwise more conformal anatomic-based CTVs were determined and described. Spinal instrumentation was consistently excluded from the CTV. We provide consensus contouring guidelines for common scenarios in postoperative SBRT for spinal metastases. These consensus guidelines are subject to clinical validation.